INTERAKSI SOSIAL ANTARUMAT BERAGAMA DI DESA NANIA, KOTA AMBON, PROVINSI MALUKU - Alce Albartin Sapulette (DIALEKTIKA, 2019)
Abstract Religious diversity has become a necessity for the people of Indonesia, including in Maluku Province. The inter-religious social relation is created harmoniously even though in 1999 there had been a conflict in this province. However, the people of Maluku, especially in Nania village, continue to create inter-religious social relations. The relation is proven through the interaction between fellow religious people. According to Emile Durkheim, social interaction is a social fact which in essence will result a social solidarity. Solidarity emphasizes on the relations between individuals and groups and underlies the common attachment in life which is supported by moral values and beliefs in the society. The real manifestation of the relationship will produce an emotional experience, thus strengthening the relationship between them. The Durkheim's view became evident in the social life of the people in Nania Village, Ambon City. Keywords: diversity, relations, social, religion, Ambon city, Maluku.